Synthesis, Characterization and Anticancer Activity of Poly Acetal /PVP Ag, Au Nanocomposite in Treatment of Lung Cancer Cell Line - A. Younus, Maha; J. Hadi , Dalia (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
In this research, poly acetal has been prepared from poly vinyl alcohol reaction with the para methyl benzaldehyde. The solution casting process was used to create the polymer blends of poly acetal and PVP. The aim of this study is to investigate the influence of the gold and silver nanoparticles on the anticancer activity of the prepared compounds. Using onion peel extract as a reducing agent, the gold nanoparticles (AuNPs) and silver nanoparticles (AgNPs) were created. Nanocomposite were prepared by solution casting by mixing poly acetal /PVP /Au, Ag nano particles with different ratios. The AuNPs And AgNPs were characterized through XRD analysis and FESEM microscopy. The poly acetal, polymer blends and nano composite were characterized by FTIR, FESEM, DSC and TGA. The FTIR has been used to analyze poly acetal, which confirms its production by displaying a new band of absorption at 1105 cm-1 due to the (O-C-O). The thermal stability of the generated polymer blends and nanocomposites is confirmed by DSC and TGA; in comparison to blends, nanocomposites have demonstrated good performance in suppressing lung cancer cell lines.